2015
DOI: 10.1186/s12931-015-0250-2
|View full text |Cite
|
Sign up to set email alerts
|

Aclidinium bromide and formoterol fumarate as a fixed-dose combination in COPD: pooled analysis of symptoms and exacerbations from two six-month, multicentre, randomised studies (ACLIFORM and AUGMENT)

Abstract: BackgroundThe combination of aclidinium bromide, a long-acting anticholinergic, and formoterol fumarate, a long-acting beta2-agonist (400/12 μg twice daily) achieves improvements in lung function greater than either monotherapy in patients with chronic obstructive pulmonary disease (COPD), and is approved in the European Union as a maintenance treatment. The effect of this combination on symptoms of COPD and exacerbations is less well established. We examined these outcomes in a pre-specified analysis of poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 37 publications
5
130
0
5
Order By: Relevance
“…В ис следованиях TOnado 1 и TOnado 2 продемонстриро вано снижение числа обострений ХОБЛ на фоне терапии тиотропием / олодатеролом по сравнению с монотерапией олодатеролом (ОР -0,83; 95% ный ДИ -0,71-0,99), но не с тиотропием [95]. В исследо ваниях, посвященных комбинации формотерол / ак лидиний (ФОР / АКЛ) не показано достоверных раз личий по числу обострений между терапией ФОР / АКЛ, монокомпонентами и САЛ / ФЛУ [96][97][98][99]. При терапии комбинацией вилантерол / умеклиди ний также не показано достоверного влияния на риск обострений при сравнении с терапией моно компонентами или тиотропием [100].…”
Section: фиксированные комбинации ддба и ддахпunclassified
“…В ис следованиях TOnado 1 и TOnado 2 продемонстриро вано снижение числа обострений ХОБЛ на фоне терапии тиотропием / олодатеролом по сравнению с монотерапией олодатеролом (ОР -0,83; 95% ный ДИ -0,71-0,99), но не с тиотропием [95]. В исследо ваниях, посвященных комбинации формотерол / ак лидиний (ФОР / АКЛ) не показано достоверных раз личий по числу обострений между терапией ФОР / АКЛ, монокомпонентами и САЛ / ФЛУ [96][97][98][99]. При терапии комбинацией вилантерол / умеклиди ний также не показано достоверного влияния на риск обострений при сравнении с терапией моно компонентами или тиотропием [100].…”
Section: фиксированные комбинации ддба и ддахпunclassified
“…In a pre-specified analysis of pooled data from two 24-week, double-blind, parallel-group, active-and placebo-controlled, multicentre, randomised Phase III studies (ACLIFORM and AUGMENT), overall, 55.7% of patients achieved the minimum clinically important difference in TDI focal score with aclidinium, compared with 57.0% with formoterol and 40.3% with placebo [14].…”
Section: Expert Review Of Clinical Pharmacologymentioning
confidence: 99%
“…The pooled analysis of the ATTAIN and AUGMENT studies showed that the percentage of patients achieving a reduction in E-RS total score of ≥2 units was 41.3% with aclidinium, compared with 42.3% with formoterol and 34.4% with placebo [14]. The same pooled analysis documented that improvements in overall night-time symptom severity (aclidinium: -0.16 units; formoterol: −0.19 units) and early-morning symptom severity (aclidinium: −0.14 units; formoterol: −0.17 units) were almost identical [14].…”
Section: Expert Review Of Clinical Pharmacologymentioning
confidence: 99%
“…Some also have a positive effect on exacerbation rates, healthcare utilisation and, possibly, mortality [93,94,96,[113][114][115][116][117][118]. One study highlighted the fact that bronchodilators predominantly exert their effects on measures of resting hyperinflation, even when little or no change in FEV1 is observed [37].…”
Section: Treatmentmentioning
confidence: 99%